Three-dimensional multispectral optoacoustic mesoscopy reveals melanin and blood oxygenation in human skin in vivo - Schwarz, Mathias; Buehler, Andreas; Aguirre, Juan; Ntziachristos, Vasilis (Journal of Biophotonics, 2016)
Optical imaging plays a major role in disease detection in dermatology. However, current optical methods are limited by lack of three-dimensional detection of pathophysiological parameters within skin. It was recently shown that single-wavelength optoacoustic (photoacoustic) mesoscopy resolves skin morphology, i.e. melanin and blood vessels within epidermis and dermis. In this work we employed illumination at multiple wavelengths for enabling three-dimensional multispectral optoacoustic mesoscopy (MSOM) of natural chromophores in human skin in vivo operating at 15-125 MHz. We employ a per-pulse tunable laser to inherently co-register spectral datasets, and reveal previously undisclosed insights of melanin, and blood oxygenation in human skin. We further reveal broadband absorption spectra of specific skin compartments. We discuss the potential of MSOM for label-free visualization of physiological biomarkers in skin in vivo. Cross-sectional optoacoustic image of human skin in vivo. The epidermal layer is characterized by melanin absorption. A vascular network runs through the dermal layer, exhibiting blood oxygenation values of 50-90%. All scale bars: 250 μm.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dermatology; Diagnostic imaging; Optoacoustic techniques; Photoacoustic techniques; Spectrum analysis